KARAKTERISTIK KANKER KOLOREKTAL DI RSUD DR. M. HAULUSSY AMBON TAHUN 2018 – 2021 - Papilaya, Williams; Rahawarin, Halidah; Hataul, Is Ikhsan; Leiwakabessy, Winny; Nikijuluw, Helfi; Sinanu, Juliet (PAMERI, 2024)
Colorectal cancer is a type of cancer that attacks the colon and rectum. Data from the Global Burden of Cancer (GLOBOCAN) states that colorectal cancer contributes to the death rate in the world 567,858 (5.8%) for colon cancer and rectal cancer 339,022 (3.4%), while the number of new cases of colorectal cancer is 1,931,590 (10%). This study aims to determine the characteristics of colorectal cancer patients based on age, gender, tumor location, histopathology type, and histopathology degree. This study is a quantitative descriptive research with a cross sectional approach. The number of research samples obtained was 57 people. The instrument used is a medical record. The data was analyzed using the SPSS application. The results of the study showed that the characteristics of colorectal cancer patients were the most in the age group of 50 - 64 years, as many as 25 people (45.8%), the most gender was in men, as many as 38 people (66.7%), the most cancer location was rectum with a total of 39 people (68.4%), the most histopathological classification was adenocarcinoma as many as 48 people (84.2%), the highest degree of differentiation was well differentiated as many as 43 people (73, 3%). It can be concluded that the characteristics of colorectal cancer patients are most in the age group of 50 - 64 years, gender is male, the location of the most cancer is in the rectum, the most histopathological classification is adenocarcinoma, and the most degree of differentiation is well differentiated